The Cricoid Force Necessary to Occlude the Esophageal Entrance: Is There a Gender Difference?. Issue 4 (December 2017) - Zeidan, A.M.; Salem, M.R.; Bamadhaj, M.; Mazoit, J.X.; Sadek, H.; Houjairy, H.; Abdulkhaleq, K.; Bamadhaj, N.
Abstract : ( Anesth Analg . 2017;124(4):1168–1173) Cricoid force (CF) is used to occlude the esophageal lumen and prevent regurgitation during surgery. However, excessive CF can deform the cricoid cartilage, oppose the vocal cords, interfere with tracheal tube passage, and result in ineffective gas exchange. Due to differences in cricoid plate size, women may require less CF than is recommended in the literature (at least 44 N). The authors of the present study hypothesized that gender differences exist in the necessary CF application to prevent regurgitation. Using a Glidescope video laryngoscope in anesthetized and paralyzed patients, they assessed the effectiveness of different CFs in occluding the esophageal entrance in men and women.